2017
DOI: 10.3389/fpsyt.2017.00139
|View full text |Cite
|
Sign up to set email alerts
|

Altered Gray-Matter Volumes Associated With Betel Quid Dependence

Abstract: Betel quid (BQ) is one of the most commonly consumed psychoactive substances. It has been suggested to be associated with various health issues, especially oral cancer. Evidence also points to possible decreased cognitive functions after long-term BQ chewing, such as attention and inhibition control. The present study aims to investigate the brain structure basis of BQ chewing in Hunan province of China. Twenty-five BQ chewers and 25 controls were recruited to participate in this study. Voxel-based morphormetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 69 publications
2
17
0
Order By: Relevance
“…25 BQD individuals were recruited from the outpatient department of stomatology at Xiangya Hospital of Central South University. As reported before ( 14 , 18 ), BQD individuals were diagnosed by a licensed MD level psychiatrist, according to the Structured Clinical Interview with DSM-IV criteria. Persons without use of BQ were defined as “healthy subjects,” which were recruited through a combination of targeted site sampling, advertisement, and snowball sampling referrals.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…25 BQD individuals were recruited from the outpatient department of stomatology at Xiangya Hospital of Central South University. As reported before ( 14 , 18 ), BQD individuals were diagnosed by a licensed MD level psychiatrist, according to the Structured Clinical Interview with DSM-IV criteria. Persons without use of BQ were defined as “healthy subjects,” which were recruited through a combination of targeted site sampling, advertisement, and snowball sampling referrals.…”
Section: Methodsmentioning
confidence: 99%
“…Participants were excluded if they met criteria for other substance dependence, had a medical history of any neurological or psychiatric disorder, or had claustrophobia/other disease preventing them from MRI scanning. The demographic and clinical characteristics of all participants had been reported in our previous study ( 18 ). This study was carried out in accordance with the recommendations of research ethical committee of Xiangya Hospital of Central South University of Hunan Province, Changsha, China.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, a review systematically assessed previous functional magnetic resonance imaging (fMRI) studies on BQ addiction, and suggested that a key involvement of the prefrontal cortex (PFC) in BQ dependency (21). For example, studies from our group suggested that BQ use was associated with decreased gray matter volumes in bilateral dorsolateral PFC and ventral medial PFC (22), altered white matter integrity in anterior thalamic radiation highly associated with PFC (23), and less cortical thickness in PFC (19). These neuroimaging studies proposed that the role of prefrontal cortical structures in BQ addiction, which plays an important role in cognitive behavioral and emotional changes in various kinds of addiction (24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%